Determinants of online journey and its influence on online customer satisfaction associated with online customer loyalty. (21st May 2019) - Nurlaela, Siti; Sumarwan, Ujang; Najib, Mukhamad
The purposes of this study are to identify the determinants of online journey and investigate its influence to online customer satisfaction and loyalty in the Indonesian online shop context. We develop the online journey model by Mangiaracina et al. (2009): site landing, product discovery, product presentation, cart management, and check-out. The delivery stages added to complete the journey. SEM analysis used to identify the positive influence of latent variables. The results showed that four stages of online journey had a significant positive effect on online customer satisfaction, i.e., product discovery, product presentation, cart management, and delivery. Moreover, online customer satisfactions influence the online customer loyalty significantly. It indicates that online journey important to consider in monitoring the online customer satisfaction and loyalty. The online shop companies can evaluate their service quality by online journey model. The magnitude of determinants influences can be indicator to set the customers experience improvement priorities.